2015
DOI: 10.1093/alcalc/agv052
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability of High-dose Baclofen in the Treatment of Patients with Alcohol Disorders: A Retrospective Study

Abstract: High-dose baclofen exposes patients with alcohol disorders to many adverse effects. Generally persistent, some adverse effects appear at low doses and may be dangerous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 21 publications
4
19
1
1
Order By: Relevance
“…The mean baclofen daily dose was 79.7 mg, very close to that reported in the study of Marsot et al (77.9 mg) even if higher daily doses were seen in the literature for observational follow‐up of alcoholic patients treated with baclofen . Baclofen was mainly prescribed three times a day with equally divided dosages and some patients take their highest doses in the morning despite side effects reported such as somnolence, asthenia and vertigo and craving symptoms that usually occur in the evening. Of interest, half of our patients were followed up in a Hepato‐Gastroenterology department and at least 36 patients (25%) had associated alcoholic liver disease (with a slight elevation of AST).…”
Section: Discussionsupporting
confidence: 76%
“…The mean baclofen daily dose was 79.7 mg, very close to that reported in the study of Marsot et al (77.9 mg) even if higher daily doses were seen in the literature for observational follow‐up of alcoholic patients treated with baclofen . Baclofen was mainly prescribed three times a day with equally divided dosages and some patients take their highest doses in the morning despite side effects reported such as somnolence, asthenia and vertigo and craving symptoms that usually occur in the evening. Of interest, half of our patients were followed up in a Hepato‐Gastroenterology department and at least 36 patients (25%) had associated alcoholic liver disease (with a slight elevation of AST).…”
Section: Discussionsupporting
confidence: 76%
“…Although a recent clinical trial found that HDB had a significant effect on abstinence maintenance , the sample size of that trial was small, and the results of two clinical trials with larger samples are still being awaited . Moreover, HDB is known to induce frequent neuropsychiatric adverse drug reactions, such as sedation, dizziness, insomnia, and tinnitus . More rarely, seizures, manic symptoms, and baclofen withdrawal syndromes have been associated with HDB .…”
Section: Resultsmentioning
confidence: 99%
“…5,6 In a recent retrospective survey including 116 patients receiving high-dose baclofen, the most frequently noted adverse effects involved disruption of the wake-sleep cycle, with 52% of patients reporting somnolence. 18 In the Baclofen for the Treatment of Alcohol Dependence (BACLAD) study, 6 sleep disturbances and fatigue were reported in 32% and 46% of patients, respectively, taking baclofen. However, none of these studies included sleep recordings.…”
Section: Cheyne-stokes Respiration None Nonementioning
confidence: 99%